Autonomous mobile robots and multi-robot systems : motion-planning, communication, and swarming - Kagan, Eugene (Wiley, 2020)
"Autonomous Mobile Robots and Multi-Robot Systems: Motion-Planning, Communication and Swarming covers the methods and algorithms for navigation, motion planning and control of mobile robots acting individually and in groups. Following recent challenges in locomotion, communication and control, the book addresses methods of positioning in global and local coordinates systems, off-line and on-line path-planning, sensing and sensors fusion, algorithms of obstacle avoidance, swarming techniques and cooperative behavior. Autonomous Mobile Robots and Multi-Robot Systems: Motion-Planning, Communication and Swarming provides a theoretical and practical guide to the navigation of mobile robots. It is self-contained and includes ready-to-use algorithms, numerical examples and simulations, which can be directly implemented in both simple and advanced mobile robots. It is also accompanied by a website hosting codes, videos and powerpoint slides"-- Provided by publisher.
Keywords: Mobile robots -- Automatic control.; Multiagent systems.; Swarm intelligence.; elektronické knihy; electronic books